Interaction Diffusion and Fertility Transition in Costa Rica - Rosero Bixby, Luis (1994)
A long-standing concern of sociologists is the contribution of diffusion processes to social change. This article considers the contribution of social interaction diffusion to the fertility transition in Costa Rica, focusing on person-to-person contagion. Several prominent features of the Costa Rican transition suggest the existence of interaction diffusion effects, notably its pervasiveness toward all socioeconomic strata and the lack of evidence of a downward shift in family size preferences. Maps of the timing of fertility transition show an ordered spatial pattern suggestive of contagion between neighboring areas. A dynamic regression model estimated from pooled time series data for 100 counties reveals inter- and within-county diffusion effects on birth control adoption net of socioeconomic and family-planning program effects.